HUBUNGAN TERPAAN IKLAN LAYANAN TRANSPORTASI ONLINE DAN ONLINE CONSUMER REVIEW DENGAN MINAT MENGGUNAKAN LAYANAN TRANSPORTASI ONLINE - Wimala Wimardana; Joyo Nur Suryanto Gono; Lintang Ratri Rahmiaji (Interaksi Online, 2023)
Maxim is one of the companies engaged in online transportation services in Indonesia since 2018. Since then, Maxim has managed to attract more than 10 million active users. This figure is quite high considering that Maxim only uses one platform; Instagram in his advertising activities. On the other hand, there is an interesting thing listed in Maxim's Instagram comment column – @Maxim_Indo – which is that reviews are often found after bad reviews about Maxim's performance. Therefore, this study aims to determine the relationship between exposure to online transportation service advertisements and Online Consumer Review (OCR) with interest in using online transportation services. This study uses the Buyer Information Environment Theory, the sample set is 125 respondents with the criteria of being 18 – 34 years old, domiciled in Semarang, and has seen Maxim's advertisements on Instagram @Maxim_Indo. This study uses non-probability sampling with accidental sampling technique. This study resulted in a significance value between exposure to online transportation service advertisements and interest in using online transportation services of 0.000, which is less than a significance value of 0.01 which means it is very significant and a correlation coefficient value of 0.254 which means that the two variables have a weak relationship and has a positive direction. This means that if exposure to online transportation service advertisements has increased, the interest in using online transportation services will also increase. On the other hand, if exposure to online transportation service advertisements has decreased, the interest in using online transportation services will also decrease. Then, in the second hypothesis correlation test, there is a relationship between OCR and interest in using online transportation services which is indicated by a significance value of 0.001 which means it is very significant because it is less than a significance value of 0.01, has a correlation coefficient value of 0.209, which means that the two variables have a weak relationship and has a positive direction. This means that if the OCR increases, the interest in using online transportation services will also increase. On the other hand, if the OCR decreases, the interest in using online transportation services will also decrease.